Level of conus medullaris termination in adult Kashmiri population: a magnet resonance imaging-based study - Neha Zahoor, Sheikh; Rashid, Baseerat; Nazir, Sabia; Ahmad Khan, Naseer; Khan, Javed Ahmad; Mubashir Yousuf, Syed; Bhat, Ghulam Mohammad (International Journal of Research in Medical Sciences, 2023)
Background: The spinal cord is considered as the principle content of vertebral canal. It begins as a downward extension of medulla oblongata at the level of upper border of first cervical vertebrae (C1). The terminal part of spinal cord is conical and is termed as conus medullaris. In adults the level of termination of conus medullaris varies between T12 to L3 vertebrae. The level of termination of conus medullaris is clinically important to avoid injuries during spinal anaesthesia and lumber puncture. Methods: The saggital magnetic resonance images of 168 patients were reviewed in the Department of Radiodiagnosis, Government Medical College, Srinagar from January 2022 to June 2022. The most caudal point of the cord was considered as the tip of conus medullaris. A line was drawn through the tip perpendicular to the long axis of spinal cord to determine its location with adjacent vertebra. Results: The level of conus medullaris termination was most commonly located at T12-L1 intervertebral disc level. The results revealed a significant statistical difference in levels of termination of conus medullaris with respect to age and sex. Conclusions: In literature, the highest level of conus medullaris termination is stated to be at T11-T12 Intervertebral disc and the lowest level at the body of L3 vertebra. Therefore, spinal anaesthesia and lumber puncture procedure should be done below L3 vertebral body in order to avoid iatrogenic complications.